2018
DOI: 10.1038/s41594-018-0056-2
|View full text |Cite
|
Sign up to set email alerts
|

Iron homeostasis regulates facultative heterochromatin assembly in adaptive genome control

Abstract: Iron metabolism is critical for sustaining life and maintaining human health. Here, we find that iron homeostasis is linked to facultative heterochromatin assembly and regulation of gene expression during adaptive genome control. We show that the fission yeast Clr4/Suv39h histone methyltransferase is part of a rheostat-like mechanism, in which transcriptional up-regulation of mRNAs in response to environmental change provides feedback to prevent their uncontrolled expression through heterochromatin assembly. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…In addition, we examined islands of facultative heterochromatin that accumulate H3K9me2 in response to stress 30 and detected three islands enriched in H3K9me2 in spH2A.W At , but not in WT and spH2A.W4A At (Figures 4E and 4F). These heterochromatin islands are distinct from that forming in response to cold in the WT, 31 but considering that spH2A.W At confers resistance to cold treatment, it might change the adaptative genome control shown previously. 31 It would be interesting to investigate the formation of heterochromatin islands and adaptative response of the genome in cold and other stress conditions conferred by spH2A.W At .…”
Section: H2aw Impacts the Boundary Between Euchromatin And Heterochrmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, we examined islands of facultative heterochromatin that accumulate H3K9me2 in response to stress 30 and detected three islands enriched in H3K9me2 in spH2A.W At , but not in WT and spH2A.W4A At (Figures 4E and 4F). These heterochromatin islands are distinct from that forming in response to cold in the WT, 31 but considering that spH2A.W At confers resistance to cold treatment, it might change the adaptative genome control shown previously. 31 It would be interesting to investigate the formation of heterochromatin islands and adaptative response of the genome in cold and other stress conditions conferred by spH2A.W At .…”
Section: H2aw Impacts the Boundary Between Euchromatin And Heterochrmentioning
confidence: 72%
“…These heterochromatin islands are distinct from that forming in response to cold in the WT, 31 but considering that spH2A.W At confers resistance to cold treatment, it might change the adaptative genome control shown previously. 31 It would be interesting to investigate the formation of heterochromatin islands and adaptative response of the genome in cold and other stress conditions conferred by spH2A.W At .…”
Section: H2aw Impacts the Boundary Between Euchromatin And Heterochrmentioning
confidence: 72%
“…A recent study showed that, despite its presence at DSR genes, Clr4 is not involved in regulating mRNA levels at normal growth temperature, whereas Set1-mediated www.nature.com/scientificreports www.nature.com/scientificreports/ deacetylation by Clr3 and other HDACs plays a key role 52 . However, loss of Clr4 in cells cultivated at 18 °C alters meiotic gene silencing but also the assembly of new facultative heterochromatin islands indicating a critical role for Clr4 at lower temperature 53 . Since Abo1 deletion have been show to affect the global gene expression and nucleosome occupancy in vivo 38 , we cannot rule out the possibility that Abo1 acts across the genome affecting indirectly the gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is based on the studies using K∆::ura4 + off allele [75,89]. In addition to ura4 + , ade6 + gene is a widely used reporter in S. pombe for RNAi-dependent and independent heterochromatin formation at centromeric regions and the mating-type locus [29,77,90,91]. When the K region is replaced by an ade6 + reporter gene, the reporter gene can be silenced by heterochromatin (K∆::ade6 + off) [29].…”
Section: The Role Of Lsd Proteins In Maintenance and Re-establishmentmentioning
confidence: 99%